Using Minerals and Industrial By-Products for High Performance Concrete for Better Performance and High Strength (International Journal of Innovative Research in Engineering & Management, 2022)
The evident truth is that concrete is the  most generally involved building material for a wide range  of exercises in the development business overall and will  keep going for a really long time. In the past few decades, fabrication of high performance concrete(HPC) has  attracted the attention of many researchers worldwide. High  performance concrete is that concrete in which the working  of concrete is better to that of ordinary concrete in terms of  durability and strength properties. This research article  derived its motivation from the fact that fabrication of HPC  with factory made derivatives not only ensures high  strength and durability but also is eco-friendly in nature. As  a result, the principle admixtures used in this research are:  Silica Dust, Residual ash and Steel Slag Aggregate. A range  of tests (tests of Resistance of acid, test for Resistance of  salt, sulphate and tests of water absorption)have been  performed to observe the properties of admixtures prepared.  Results show that SFSSAC, RASSAC, SFRAC and  SFRASSAC admixture outperforms the other CC blend and  seems to be very promising in the near future.
Keywords: Concrete; Strength; Durability; Factory Made Derivatives